Comparison of ethyl cellulose–gelatin composite films fabricated by electrospinning versus solvent casting. Issue 46 (9th September 2018) - Liu, Yuyu; Deng, Lingli; Zhang, Cen; Chen, Kailun; Feng, Fengqin; Zhang, Hui
ABSTRACT: In this study, we fabricated ethyl cellulose (EC)–gelatin (G) composite films by solvent casting and electrospinning. The characterization of the cast and electrospun films was performed by scanning electron microscopy, differential scanning calorimetry, thermogravimetric analysis, X‐ray diffraction, Fourier transform infrared spectroscopy, X‐ray photoelectron spectrometry, and water contact angle measurements. The results showed that the blending of EC with G improved the spinnability of the composite films with higher thermal stability. Compared with solvent casting, electrospinning induced a helix‐to‐coil transition of G and provided more hydrogen‐forming sites for EC to form a compatible network. Interestingly, the electrospun composite film had a hydrophobic surface with a water contact angle of 113.8°, whereas the cast composite film showed a hydrophilic surface at 67.5°. The confocal laser scanning microscopy observations suggested that after water immersion, the cast composite film collapsed into aggregates, whereas the electrospun composite film maintained the nanofibrous structures well; this indicated an improved water resistance. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46824. Abstract :